119k views
5 votes
For any nonnegative real number.

For any nonnegative real number.-example-1

1 Answer

3 votes

Answer:

A

Explanation:

We know that
√(b)=b^(1/2).

We also know that
(a^b)^c=a^(bc).

We can combine these facts to get
(√(b))^2=(b^(1/2))^2=b^(1/2*2)=b^(1)=b.

So, the answer is
\boxed{A} and we're done!

Note: the non-negative part or the equation comes from the fact that you assume the square root of a negative number doesn't exist. You will change this assumption later in the year, or in further years.

User Ymg
by
5.8k points